2018
DOI: 10.21608/jpp.2018.35501
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Responses of Sweet Pepper (Capsicum annum L.) to Organic and NPK Mineral Fertilization under Plastic Houses Conditions at Arid Regions

Abstract: Two greenhouse experiments were conducted during 2014/ 2015 and 2015/2016 seasons in the Experimental Station Farm, Faculty of Agriculture and Natural Resources, Aswan University, Egypt on a sandy textured soil under unheated plastic houses. The target fertilization program seeks to achieve the best combination of various organic and NPK mineral fertilization that lead to the highest yield and quality of produced sweet pepper plant ''Lama Star F 1 hybrid'' especially during the winter season. Therefore, 12 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The distance between plants was 50 cm. The organic fertilizer (48 m 3 /ha) was added at soil preparation, whereas the chemical fertilizers were added in three equal doses as recommended (NPK, 238:95:190 kg/ha), the first dose was added at soil preparation, the second was added at 30 days after transplanting and the third at the beginning of flowering stage [24]. Plants were irrigated from the well with saline water __________________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Growth Conditionsmentioning
confidence: 99%
“…The distance between plants was 50 cm. The organic fertilizer (48 m 3 /ha) was added at soil preparation, whereas the chemical fertilizers were added in three equal doses as recommended (NPK, 238:95:190 kg/ha), the first dose was added at soil preparation, the second was added at 30 days after transplanting and the third at the beginning of flowering stage [24]. Plants were irrigated from the well with saline water __________________________________________________________________________________________________________________ ________________________________________________ Egypt.…”
Section: Growth Conditionsmentioning
confidence: 99%
“…This was in line with the highest specific leaf area in MP3 indicating a low shoot weight divided by the root portion so that a low shoot-root ratio was obtained. A report by Alkharpotly (2018) on Capsicum annum L. showed that the combination of 20 tons organic chicken manure per ha combined with inorganic fertilizer was the optimal combination treatment resulting in the best average value of vegetative growth characters. The results of another study showed that the application of various organic fertilizers without a combination of inorganic fertilizers did not give a positive response to the growth of shallots (Suwandi et al, 2015;Arifin & Mujoko, 2019).…”
Section: Discussionmentioning
confidence: 99%